Psychological, Linguistic, Communicative Characteristics of Reading - Kazakova Dilora Gaffarovna (Genius Journals, 2021)
This article explores the role and importance of reading. As you know, practical knowledge of the language lies primarily in the ability of the student to apply the acquired skills and abilities in their work. Reading helps and contributes to improving other types of speaking (speaking, listening, writing) as well as maintaining knowledge of the language being learned, especially speaking skills. Practical language skills consist in the ability of students to apply the knowledge and skills they have acquired in the language in their professional activities [1]. The purpose of reading should be to get information and the motive should be to meet the need for information.
Keywords: Reading; process of perception; a content plan; a procedural plan